Desenvolvendo o Raciocínio Proporcional - Souza, Evaldo Fernandes de (2021)
Considering that proportionality is a concept with applications in several areas of knowledge and daily use, we will present a didactic sequence to favor the development of proportional reasoning, through a series of activities that involve comparing and determining the equivalence of reasons and resolving proportions in varied contexts without the use of rules, nomenclatures or formulas.